Batteriespeicher in Haushalten unter Berücksichtigung von Photovoltaik, Elektrofahrzeugen und Nachfragesteuerung - Kaschub, Thomas (Produktion und Energie / Karlsruher Institut für Technologie, Institut für Industriebetriebslehre und industrielle Produktion u. Deutsch-Französisches Institut für Umweltforschung, 2017)
In this work a newly developed techno-economic optimization model of a household system with electric vehicle (EV) is used to endogenously dimension both the PV system and the stationary battery storage system (SBS). It maximizes the net present values (NPV) of these two systems. The NPV are highly affected by the load shifting potentials of EV and SBS, electricity tariff design and further general conditions.